Writing medical comics. (3rd July 2019) - Waite, Miriam
Abstract: The emergent field of medical comics is being lauded as a way to visually communicate medical information to patients more effectively than current methods. However, there is very little advice available in the literature as to how to design them. This comics article attempts to address some questions you might have when starting a medical information comic. It talks about designing comics for novice comics readers; what sort of colours to use (if any); character choice and anthropomorphism; the length of the narrative; and the use of humour. Essentially it advocates simplicity, while overcomplicating everything.